Tanggung Jawab Hukum Dokter Dalam Pelayanan Kesehatan Oleh Perawat Terhadap Klien (Pasien) - Sudjana Sudjana (Faculty of Law, Andalas University, 2022)
This study aims to determine the legal relationship of doctors, nurses, and patients as well as the principle of legal responsibility of doctors in health services by nurses to patients. The approach method used is normative juridical with emphasis on secondary data, namely primary, secondary, and tertiary legal materials. Study results: (1). The legal relationship between doctors and nurses is based on delegation and mandate attribution. The nurse and client relationship is interpersonal and professional, which is subject to the Nursing Act. The doctor and patient relationship is based on the theurapetic transaction through voluntary representation (Article 1354 of the Civil Code) and the validity of the agreement (Article 1320 of the Civil Code). (2). Legal responsibility related to the mandate given by the doctor to the nurse remains with the doctor, so that if the action taken by the nurse is not in accordance with the SOP it becomes the nurse's responsibility in accordance with the principle of liability based on fault. However, doctors are responsible based on the principle of vicariuos liability. Whereas in the delegation, if the nurse's actions are not in accordance with the SOP and cause patient losses, the responsibility of the nurse is in accordance with the principle of liability based on fault. If health services by nurses are in accordance with the SOP but cause harm to patients both in the mandate and delegation, doctors and nurses are not responsible because it is a medical risk.